2018
DOI: 10.1016/j.vaccine.2018.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Myocarditis and pericarditis are rare following live viral vaccinations in adults

Abstract: Reports of myocarditis and pericarditis following smallpox vaccination in adults suggested a need to assess inflammatory cardiac disease risk among adults who receive live viral vaccinations. From 1996 through 2007, among 416,629 vaccinated adults in the Vaccine Safety Datalink, we identified one probable pericarditis case and no cases of myocarditis in the 42 days following a live viral vaccination. Our self-controlled risk interval analysis found that, based on one case identified during the risk interval an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 16 publications
2
46
1
4
Order By: Relevance
“…Myocarditis as an adverse reaction to the COVID-19 vaccine : In general, myocarditis, is considered an uncommon adverse event following immunization [6] , [7] , [8] . An exception to this generalization is myocarditis following smallpox vaccination in adults with a reported incidence of 1:10,000 [7] , [9] , [10] , [11] , [12] .in a prospective safety surveillance study of perimyocarditis following smallpox vaccine , the authors report that most of the identified cases of perimyocarditis were subclinical and were identified through routine pre and post vaccination troponin level measurments [13] . This finding raises concern that we identified only the “tip of the icberg” i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Myocarditis as an adverse reaction to the COVID-19 vaccine : In general, myocarditis, is considered an uncommon adverse event following immunization [6] , [7] , [8] . An exception to this generalization is myocarditis following smallpox vaccination in adults with a reported incidence of 1:10,000 [7] , [9] , [10] , [11] , [12] .in a prospective safety surveillance study of perimyocarditis following smallpox vaccine , the authors report that most of the identified cases of perimyocarditis were subclinical and were identified through routine pre and post vaccination troponin level measurments [13] . This finding raises concern that we identified only the “tip of the icberg” i.e.…”
Section: Discussionmentioning
confidence: 99%
“…However, this cardiac association appears unique to the smallpox vaccine as Kuntz and colleagues recently found the occurrence of myopericarditis following other live viral vaccines is rare with an estimated incidence of 0.24 per 100,000 vaccinated which is not higher than the background rate and is much lower than the incidence rates reported following smallpox vaccination. 44 Interestingly, a recent report of an automated study conducted using data on 11,374 insured patients in Taiwan aged 20 years and older found influenza infection was significantly associated with the development of atrial fibrillation, with an 18% increase in the risk, which could be reduced through influenza vaccination. 23 A follow up study from the same research group has also suggested influenza vaccination may be effective in reducing the risk of ischemic stroke in patients aged greater than 65 years with atrial fibrillation.…”
Section: Discussionmentioning
confidence: 99%
“…Myocarditis has also been reported following live viral vaccinations, most notably the smallpox vaccine. From the early 1950s until 2003, six cases of cardiac complications following smallpox vaccination were reported in the United States [ 4 ]. A campaign to vaccinate U.S. military personnel against smallpox with the DryVax vaccine between 2002 and 2003 resulted in 67 cases of myocarditis or pericarditis out of the 540,824 personnel vaccinated [ 5 ].…”
mentioning
confidence: 99%
“…A campaign to vaccinate U.S. military personnel against smallpox with the DryVax vaccine between 2002 and 2003 resulted in 67 cases of myocarditis or pericarditis out of the 540,824 personnel vaccinated [ 5 ]. Due to concern for cardiac complications following smallpox vaccination, a study was conducted to evaluate risk of myocarditis and pericarditis in live viral vaccinations [ 4 ]. Of the 416,629 vaccinated adults studied, only one case of pericarditis and zero cases of myocarditis were identified following vaccination [ 4 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation